Indicating Ahead: Best Execution and the NASDAQ Preopening - Ciccotello, Conrad S.; Hatheway, Frank M. (Journal of Financial Intermediation, 2000)
Dealers enter nonbinding expressions of interest during the Nasdaq preopening to promote price discovery and ease stock inventory management when the market opens. But does this practice of “indicating ahead” constitute best execution for an individual customer? Arguments in favor of the practice rely on the notion that best execution is a general condition as opposed to a concept applicable on a trade-by-trade basis. Some customers must sacrifice in individual instances to improve the functioning of the overall market. But the practice of indicating ahead violates the dealer agent's duty of loyalty to her individual customer. Moreover, the dealer's financial self-interest is best served by indicating ahead. Journal of Economic Literature Classification Numbers: G10, G18, K22.